2015
DOI: 10.1097/aci.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chronic rhinosinusitis

Abstract: Purpose of review To review the recent literature on risk factors for chronic rhinosinusitis (CRS) with an emphasis on genetic, comorbid diseases and environmental factors associated with CRS. Through identifying potential risk factors for CRS, we glean insights into the underlying pathogenic mechanisms and essential for developing effective therapeutic strategies. Recent findings Recent findings demonstrate that genetics, comorbid medical conditions including airway diseases, gastroesophageal reflux disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 95 publications
2
39
0
2
Order By: Relevance
“…Similar associations have been reported in prior studies of CRS [3235] but not by symptom status. We found CRS subgroups were most associated with health outcomes when both smell loss and pain and/or pressure were part of the profile, while associations were weakest among CRS profiles without smell loss, pain, or pressure.…”
Section: Discussionsupporting
confidence: 90%
“…Similar associations have been reported in prior studies of CRS [3235] but not by symptom status. We found CRS subgroups were most associated with health outcomes when both smell loss and pain and/or pressure were part of the profile, while associations were weakest among CRS profiles without smell loss, pain, or pressure.…”
Section: Discussionsupporting
confidence: 90%
“…This is in accordance with the results from some studies, although no such association was found in a recent case‐control study with objectively verified CRS . There are still few studies on the effect of environmental factors on CRS, but there are some results indicating that air pollution, the use of woodstoves as principal source of heat and exposure to gas, fumes and dust at work may be related to an increased risk of CRS . Our results contribute another predisposing and preventable risk factor, showing that dampness at home is strongly related to CRS.…”
Section: Discussionsupporting
confidence: 92%
“…16 There are still few studies on the effect of environmental factors on CRS, but there are some results indicating that air pollution, the use of woodstoves as principal source of heat and exposure to gas, fumes and dust at work may be related to an increased risk of CRS. 24 Our results contribute another predisposing and preventable risk factor, showing that dampness at home is strongly related to CRS. Dampness was found to have an impact on CRS, which was as strong as smoking, and the effects were seen to be additive when both risk factors existed.…”
Section: Discussionmentioning
confidence: 52%
“…Both CRS phenotypes also can be associated with autoimmune diseases, such as Wegener’s granulomatosis and sarcoidosis. 23 …”
Section: Phenotypes and Endotypesmentioning
confidence: 99%